3D virtual reality-based driver test platform with multiple driving simulator - Woo, Charlotte Huai Min (Nanyang Technological University, 2023)
Driving simulators are widely known to be used for leisure and for various research purposes. A driver’s driving style can be studied and determined without doing real-world driving experiments. This has been done by many research groups with the use of a single simulator-based driver test platform, consisting of a steering wheel and pedals as the basic testbed. Preliminary studies of multiple driving simulators have been done to simulate real-world driving and understand how drivers’ behaviour affects one another on the road. In addition, the study and integration of virtual reality (VR) head-mounted display (HMD) could improve the realism of the set-up. The added immersion could ensure reliability and accuracy of data collected from volunteers driving the simulator. Using the volunteer’s raw data collected and extracted from the driving simulation, further analysis was completed using python to generate the corresponding jerk profiles, so that the classification of driving styles could be determined. Further studies could be done to understand the importance and impact of how these data can be used to benefit drivers, organisations and the environment